2019
DOI: 10.1016/j.neurobiolaging.2018.10.014
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo visualization of age-related differences in the locus coeruleus

Abstract: The locus coeruleus (LC), the major origin of noradrenergic modulation of the central nervous system, may play an important role in neuropsychiatric disorders including Parkinson's disease and Alzheimer's disease. The pattern of age-related change of the LC across the life span is unclear. We obtained normalized, mean LC signal intensity values, that is, contrast ratios (CRs), from magnetization transfer–weighted images to investigate the relationship between LC CR and age in cognitively normal healthy adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
210
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(241 citation statements)
references
References 45 publications
25
210
6
Order By: Relevance
“…Furthermore, we found no significant relation between CNR and age. The relation between LC intensity and age, although found in several studies, could not be replicated by others (Liu et al, 2019;Shibata et al, 2006). On the other hand, we had a relatively short age range in our sample, which may be a reason why we did not find a significant correlation with age.…”
Section: Lc Intensity Values and Correlation With Agecontrasting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, we found no significant relation between CNR and age. The relation between LC intensity and age, although found in several studies, could not be replicated by others (Liu et al, 2019;Shibata et al, 2006). On the other hand, we had a relatively short age range in our sample, which may be a reason why we did not find a significant correlation with age.…”
Section: Lc Intensity Values and Correlation With Agecontrasting
confidence: 74%
“…LC signal intensity was extracted from each individual's neuromelanin sequence according to a standard procedure (Betts et al, 2017;Clewett et al, 2016;Liu et al, 2019;Sasaki et al, 2008;Shibata et al, 2006). First, on the axial slices where LC anatomical position was expected (Keren et al, 2009;Keren et al, 2015) we identified the voxel of highest intensity in each lateral side.…”
Section: Signal Intensity Extractionmentioning
confidence: 99%
“…These paramagnetic effects can be leveraged by nmT1 imaging to increase the contrast of neuromelanin containing voxels to allow for the visualization and localization of the LC in structural MRI scans (Keren et al, 2009). Because regions that contain more neuromelanin appear brighter in nmT1 images, it also provides an in vivo measure of the amount of neuromelanin in the LC (and the other neuromelanin containing region in the brainstem, the substantia nigra) (e.g., Keren et al, 2009;Keren et al, 2015;Liu et al, 2019).…”
Section: Localizing Human Lc and Measuring Its Neuromelanin Content Umentioning
confidence: 99%
“…Previous work has reported age-related differences in LC contrast (Betts et al, 2017, Liu et al, 2019, Clewett et al, 2016) and suggested that the variation of the contrast during ageing was consistent with the concentration of neuromelanin in the LC (Zecca et al, 2004). Some studies also reported that age-related effects can confound the reference region selection by introducing biased baseline measures (Keren et al, 2009, Clewett et al, 2016).…”
Section: Methodsmentioning
confidence: 76%
“…Finally, we examined the effect of age on the LC contrast. The impact of ageing on LC signal has been previously been assessed (i) by showing the group difference between young and older adults (Clewett et al, 2016, Betts et al, 2017, Dahl et al, 2019), or (ii) by testing for a linear and quadratic function of age across the life-span (Shibata et al, 2006, Liu et al, 2019). The results are consistent with the accumulation of neuromelanin with age (Zecca et al, 2004).…”
Section: Discussionmentioning
confidence: 99%